Longitudinal association of biological maturation with physical activity behaviors in girls transitioning from 5th to 7th grade. Issue 7 (25th February 2022) - Pate, Russell R.; Dowda, Marsha; Dishman, Rod K.; Gorab, Joseph; Bucko, Agnes; Saunders, Ruth P.
Abstract: Introduction: This longitudinal study determined if social cognitive variables influence physical activity in girls stratified on the basis of maturity status. Methods: Participants attended South Carolina public schools (Mage in 5th grade = 11.1 years) and included a cohort of 529 girls who provided physical activity data in the 5th grade and in 6th and/or 7th grade. The measure of maturity status was age at peak height velocity (APHV) estimated from maturity offset when the children were in the 5th grade. The Earlier Maturity (EM) group included girls whose APHV was one standard deviation or more below the mean APHV for the full sample. All other girls were placed in the Later Maturity (LM) group. Physical activity was assessed at each time point via accelerometry. Social‐cognitive variables were assessed at each time point by a questionnaire measuring self‐efficacy, enjoyment, competence, appearance, fitness, and social motives for physical activity. Growth curves for the total, Earlier Maturing, and Later Maturing groups assessed relationships between physical activity over time and time‐varying social cognitive variables. Results: Physical activity was lower in the Earlier Maturing group and was positively associated with self‐efficacy and enjoyment motivation in the total group. These relationships were observed in the 5th grade and maintained through 7th grade. In the Later Maturing group, we observed positive relationships between physical activity and self‐efficacy, enjoyment and competence motivation. Conclusions: Strategies to increase confidence, skills, and enjoyment of physical activity may only be effective for promoting activity among later maturing girls.